Selected Properties of Peat Degradation on Different Land Uses and the Sustainable Management - M. Edi Armanto; Elisa Wildayana; M.S. Imanudin; Heri Junedi; Mohd. Zuhdi (Center for Journal Management and Publication, 2017)
The research aimed to analyze selected properties of peat degradation on different land uses and the sustainable management. The research area is located in the lowland dome peats in the catchment basin of Sibumbung River and Sibotak River in Sub District of East Pedamaran, OKI South Sumatra. The research method used an experimental design of Randomized Completely Block Design with two Blocks and five treatments (Site A: intercropping between oil palm and pineapples; Site B: oil palm plantations, Site C: peat forest; Site D: swamp bush; Site E: swamp grass). The research resulted that drainage and land uses decrease some properties of peats, namely C/N ratio, total pore space, fiber and ash content as well as organic C on cultivated peats and are significantly different at level of 5% compared with uncultivated peats. Bulk density increased due to peat compaction and groundwater table on cultivated peats, which is getting deeper, and significantly different compared with uncultivated peats. All soil series do not show any change because of drainage and different land uses. Sustainable peat management can be implemented through three approaches, namely managements of water, soil and crops.